2018
DOI: 10.1021/acsomega.8b00155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Fate of Hydrogen-Bonded Free-Radical Intermediates and Their Coupling Products from the Hydrogen Atom Transfer Agent 1,8-Naphthalenediol

Abstract: 1,8-Naphthalenediol (dihydroxynaphthalene, 1,8-DHN) has been shown to be a potent hydrogen atom transfer (HAT) antioxidant compound because of the strong stabilization of the resulting free radical by intramolecular hydrogen bonding. However, the properties, reactivity, and fate of the 1,8-DHN phenoxyl radical have remained so far uncharted. Herein, we report an integrated experimental and computational characterization of the early intermediates and dimer products that arise by the oxidation of 1,8-DHN. Laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…The UV-visible spectrum of the DMF suspension showed broadband absorption throughout the whole spectrum, typical of eumelanin polymers, with an intense absorption in the visible region, denoting a high degree of polymerization. Moreover, the presence of shoulders at 390, 460 and 580 nm suggested the presence of extended quinonoid moieties, as reported in a previous work, [20] indicating a high π-electron conjugation.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The UV-visible spectrum of the DMF suspension showed broadband absorption throughout the whole spectrum, typical of eumelanin polymers, with an intense absorption in the visible region, denoting a high degree of polymerization. Moreover, the presence of shoulders at 390, 460 and 580 nm suggested the presence of extended quinonoid moieties, as reported in a previous work, [20] indicating a high π-electron conjugation.…”
Section: Resultssupporting
confidence: 84%
“…Chemical studies indicated that DHN tends to polymerize via 2,2′‐, 2,4′‐ and 4,4′‐bondings to give regular patterns of oligomers that may exhibit extended quinone‐methide moieties (Figure ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that a representative oxyPAH, 1,8-dihdroxynaphthalene (1,8-DHN), undergoes polymerization to give a black, solid polymer mimicking fungal melanin (Figure 2) and displaying considerable H-atom donor behavior, coupled with strong chemical robustness toward hydrogen peroxide degradation and bleaching [16,17,18]. Thus, oxidative polymerization of hydroxylated PAHs may lead to allomelanin-like materials with suitable properties for biointerfaces, organic electronics, and theranostics [19].…”
Section: Complex Organic Moleculesmentioning
confidence: 99%
“…All three energetically favorable coupling isomers were obtained, namely para-para a, ortho-ortho b,a nd para-ortho 10 c combinations, respectively. [29] The relative amountso fd imers were found to be dependent on the nature of the meteorite;c ompounds 10 b and 10 c were generally the most abundant derivatives ( Table 1, entries 22 and 23, 45 and 46, and 59 and 60, respectively).…”
Section: Irradiation Of 1-hydroxynaphthalenementioning
confidence: 94%